2000
DOI: 10.1001/archderm.136.9.1125
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of 5α-Reductase Isozymes in Acne Lesions and Normal Skin

Abstract: Background: Dihydrotestosterone mediates androgendependent diseases, such as acne, hirsutism, and androgenetic alopecia. This hormone is produced from testosterone by the 5␣-reductase enzyme. There are 2 isozymes of 5␣-reductase (types 1 and 2) that differ in their localization within the body and even within the skin. Activity of the type 1 isozyme predominates in sebaceous glands, where it may be involved in regulation of sebum production. Since specific inhibition of 5␣-reductase type 1 may represent a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
1
35
0
1
Order By: Relevance
“…Skin cells are able to synthesise locally acting estrogens from the precursors cholesterol and DHEA (Fig. 2) (Simpson et al 1997;Bulun et al 1999;Chen et al 2002;Chen et al 1998;Thiboutot et al 1998;Hughes et al 1997;Sawaya and Penneys 1992;Dumont et al 1992;Eicheler et al 1995;Thiboutot et al 2000). Additionally, local production of 11b-HSD by epidermal keratinocytes, dermal fibroblasts and hair follicles (Tiganescu et al 2011) increases cortisol conversion and has been speculated to control the inflammatory response (Vukelic et al 2011).…”
Section: Skin Ageing and Estrogensmentioning
confidence: 99%
“…Skin cells are able to synthesise locally acting estrogens from the precursors cholesterol and DHEA (Fig. 2) (Simpson et al 1997;Bulun et al 1999;Chen et al 2002;Chen et al 1998;Thiboutot et al 1998;Hughes et al 1997;Sawaya and Penneys 1992;Dumont et al 1992;Eicheler et al 1995;Thiboutot et al 2000). Additionally, local production of 11b-HSD by epidermal keratinocytes, dermal fibroblasts and hair follicles (Tiganescu et al 2011) increases cortisol conversion and has been speculated to control the inflammatory response (Vukelic et al 2011).…”
Section: Skin Ageing and Estrogensmentioning
confidence: 99%
“…The primary 'male' sex steroid testosterone is converted to its more active metabolite 5␣-dihydrotestosterone (DHT) by the enzyme 5␣-reductase (5␣-R), of which two isoforms exist (5␣-R1 and 5␣-R2); both are expressed by hair follicles and the epidermis in uninjured skin (Eicheler et al, 1995;Thiboutot et al, 2000). Several studies have demonstrated cell-specific and differential regulation by testosterone and DHT of proteins with key roles in cutaneous repair.…”
Section: Introductionmentioning
confidence: 99%
“…M NIXON and others 115 Zyirek et al (1987) M NIXON and others . Actions of 5a-reduced glucocorticoids Price 1997, Thiboutot et al 2000, Thiele et al 2005, lungs (Normington & Russell 1992, Provost et al 2002, Kimura et al 2003, and in the gastrointestinal tract (Nienstedt et al 1980a,b, Normington & Russell 1992, all sites of importance in inflammatory diseases and GC therapies. In metabolic tissues, 5aR1 is highly expressed in the liver (Normington & Russell 1992, Livingstone et al 2005 but is also present in lower abundance in adipose (Livingstone et al 2005, Wake et al 2007), but not in human skeletal muscle (Thigpen et al 1993b).…”
Section: Therapeutic Actions Of Gcs To Relieve Inflammationmentioning
confidence: 99%